Quality of Life in Yoga Experienced and Yoga Naïve Asian Indian Adults with Obesity - Shirley Telles; Sachin Kumar Sharma; Alok Singh; Niranjan Kala; Vikas Upadhyay; Jaideep Arya; Acharya Balkrishna (Journal of Obesity)
Background. Obesity adversely affects quality of life which then acts as a barrier to weight loss and weight loss maintenance. Hence, those interventions which positively influence the quality of life along with weight reduction are considered useful for sustained weight loss in persons with obesity. An earlier study showed better quality of life in obese adults who had experience of yoga compared to yoga naïve obese adults. However, the main limitation of the study was the small sample size (n=20 in each group). Objective. The present study aimed to determine whether with larger sample sizes the quality of life would differ in yoga experienced compared to yoga naïve adults with obesity. Methods. There were 596 Asian Indian obese adults (age range 20 to 59 years; group mean age ± SD; 43.9 ± 9.9 years): of whom (i) 298 were yoga experienced (154 females; group mean age ± SD; 44.0 ± 9.8 years) with a minimum of 1 month of experience in yoga practice and (ii) 298 were yoga naïve (154 females; group mean age ± SD; 43.8 ± 10.0 years). All the participants were assessed for quality of life using the Moorehead–Ardelt quality of life questionnaire II. Data were drawn from a larger nationwide trial which assessed the effects of yoga compared to nutritional advice on obesity over a one-year follow-up period (CTRI/2018/05/014077). Results. There were higher participant-reported outcomes for four out of six aspects of quality of life in the yoga experienced compared to the yoga naïve (p<0.008, based on t values of the least squares linear regression analyses, Bonferroni adjusted, and adjusted for age, gender, and BMI as covariates). These were enjoyment in physical activities, ability to work, self-esteem, and social satisfaction. Conclusion. Obese adults with yoga experience appear to have better quality of life in specific aspects, compared to yoga naïve persons with a comparable degree of obesity.